Clonagem e expressão de uma lectina de Artocarpus incisa L. (Frutalina) em Escherichia coli - Nepomuceno, Denise Rocha (2008)
The lectins constitute biotechnological tools of fundamental importance in hystochemical and cytochemical studies for the detection of tissue glycoconjugates. Among their applications are the identification of membrane receptors and the detection of neoplastic characteristic structures. Frutalin, an -D-galactose-binding lectin from Artocarpus incise seeds, has already been used in the hystochemical detection of thyreoid and breast neoplasia. In this work was made a study of the cloning and expression of the frutalin gene in Escherichia coli Origami (DE3) cells and was determined the three-dimensional structure of this protein through homology modeling. The frutalin gene cloning was accomplished from the product on RT-PCR with seeds in distinct stages of development of the Artocarpus incisa fruits. Twelve clones were obtained, from which five were sequenced. The frutalin gene was expressed in E. coli using the pET15b expression vector. A recombinant lectin (rFrutalin) was expressed by growing the bacteria in the presence of isopropyl -D-thiogalactopyranoside 1mM. All the recombinant lectin was found in an insoluble aggregated form as inclusion bodies. The recombinant lectin had a higher molecular mass (19,2 kDa) than the native lectin (15 kDa) as estimated by SDS-PAGE and Western blot analyses, showing that the recombinant single chain Frutalin is not processed in E. coli cells. The models generated for the clones obtained indicate that the mutations do not change the molecules active sites. Mutations in the clones obtained suggest the occurrence of isoforms of this protein.